Faktor-Faktor yang Mempengaruhi Fokus dan Antusiasme Mahasiswa dalam Pembelajaran di Kelas - Sherly Wijaya; Labora Nainggolan; Elen Febriana Sinambela; Yuli Andriyani; Roiman Laia; Arya Erilian Saragih; Ikhwan El Akmal Pakpahan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to examine the dominant instructional factors that influence university students' focus and enthusiasm during classroom learning. As the use of presentation media becomes increasingly integrated into higher education, understanding which elements most effectively support student engagement is crucial. This research employed a descriptive quantitative method involving 134 students from various academic programs. Data were collected using structured questionnaires consisting of both closed-ended and open-ended items. The findings reveal that presentation media plays a supportive role by enhancing visual organization and material clarity. However, lecturer explanation emerged as the most influential factor, significantly shaping cognitive attention and emotional engagement. These results highlight that while visual design contributes to comprehension, effective communication and interaction between lecturers and students remain central determinants of engagement. The study provides valuable insights for improving instructional strategies and developing more engaging learning environments in higher education.